2023
DOI: 10.1021/jacs.3c00797
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Aspect of Displacive-Type Ferroaxial Phase Transition from Perspective of Second-Order Jahn–Teller Effect: NASICON Systems as an Example

Abstract: Ferroaxial order, characterized by a rotational arrangement of electric dipoles, attracts increasing attention in terms of a new family of ferroic orders. However, there has been no chemical guideline for exploring crystalline materials showing ferroaxial order, namely ferroaxial materials. Here, we present a chemical guideline grounded in staggered polyhedral connectivity, which we propose as a structural prerequisite for ferroaxial order, and the second-order Jahn–Teller (SOJT) theory extended from molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The SOJT activity is evaluated using the symmetry selection rule Φ 0 ⊗Φ p ⊗Φ n , where Φ 0 , Φ p , and Φ n are the irreps of the ground states, the concerned distortion mode, and the excited states, respectively. , When the direct product result contains the totally symmetric representation, the concerned interaction of their electronic states is allowed to be SOJT-active. Furthermore, the interaction between the upper-lying ground states and low-lying excited states (e.g., VBM and CBM for an insulator) strongly contributes to the SOJT activity because it is inversely proportional to the energy difference E 0 – E n ( E 0 and E n are eigen energies of the ground state and the excited state, respectively). , Using the irreps of the VBM, CBM, and ferroaxial mode, the direct product is calculated as Γ 2 + ⊗Γ 2 + ⊗Γ 1 + = Γ 1 + , including the totally symmetric representation for space group R m . This means that the electronic state of Na 2 Hf­(BO 3 ) 2 is SOJT-active under the Γ 2 + ferroaxial distortion at least from the viewpoint of orbital symmetry.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SOJT activity is evaluated using the symmetry selection rule Φ 0 ⊗Φ p ⊗Φ n , where Φ 0 , Φ p , and Φ n are the irreps of the ground states, the concerned distortion mode, and the excited states, respectively. , When the direct product result contains the totally symmetric representation, the concerned interaction of their electronic states is allowed to be SOJT-active. Furthermore, the interaction between the upper-lying ground states and low-lying excited states (e.g., VBM and CBM for an insulator) strongly contributes to the SOJT activity because it is inversely proportional to the energy difference E 0 – E n ( E 0 and E n are eigen energies of the ground state and the excited state, respectively). , Using the irreps of the VBM, CBM, and ferroaxial mode, the direct product is calculated as Γ 2 + ⊗Γ 2 + ⊗Γ 1 + = Γ 1 + , including the totally symmetric representation for space group R m . This means that the electronic state of Na 2 Hf­(BO 3 ) 2 is SOJT-active under the Γ 2 + ferroaxial distortion at least from the viewpoint of orbital symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…The SOJT theory based on molecular orbitals has successfully explained the mechanism of structural distortions with wavevector q = 0 such as molecular deformation and polar displacement of perovskite structures. Meanwhile, it has also been applied to the origin of structural distortions with a non-zero q such as a rotational displacement leading to a superlattice structure, being recognized as the general source driving structural distortions with various q . Indeed, it has been demonstrated that the chemical origin of the displacive-type ferroaxial phase transition in Na superionic conductor (NASICON) systems is described by the SOJT theory extended to electronic band structure . These results suggest to us that switching between ferroaxial and nonferroaxial structures can be tuned by SOJT activity.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…38,39 Nevertheless, the structural distortion caused by the Jahn–Teller effect hinders the diffusion of Na + ions leading to poor rate capability. 40–43 Besides, the Mn 3+ ions generated in the reaction process could transform into Mn 4+ and Mn 2+ ions under disproportionation, and the dissolved Mn 2+ in the electrolyte destroys the crystal structure with the degradation of the cathode materials, and could be deposited on the anode and catalyze the continuous growth of a solid electrolyte interphase (SEI) film, giving rise to the deterioration of full cell performance. 44–46 To make better use of the multi-electron reaction superiority of Mn ions, researchers have developed a series of Na-rich cathodes to activate the Na + ions attached to the crystal lattice to achieve high working voltage and specific capacity, such as the well-designed Na 3+ x V 2− x Mn x (PO 4 ) 3 , 18,47 Na 3+ x + y V 2− x − y Fe x Mn y (PO 4 ) 3 , 32,48 Na 3 MnTi(PO 4 ) 3 , 49,50 etc.…”
Section: Introductionmentioning
confidence: 99%